Managing Stress During Self-Isolation Using Mind Healing Technique Therapy - Chyril Futuhana Ahmad; Husnul Qodim (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2022)
At the end of 2019, the world community was shocked by the findings from the Chinese health authorities of pneumonia or pneumonia caused by a new virus variant called SARS-Cov-2 or Covid-19. The case was first discovered in Wuhan province. This virus spreads fast, and on February 2, 2020, the first case outside China was found in the Philippines. With such a fast spread, the World Health Organization WHO later declared that the Covid-19 virus was a pandemic on March 9, 2020. In Indonesia itself, the first case of Covid-19 was found on March 2, 2020. Since then, other cases have started to appear in Indonesia. Even the highest cases, several regions touched 33,772 cases, to be exact, in July 2021. Seeing this condition, President Joko Widodo then issued a government regulation on Large-Scale Social Restrictions (PSBB). In addition, those infected with the Covid-19 virus must self-isolate for at least 14 days. The policy, of course, also has a negative impact on a person, such as feelings of alienation, loneliness, anxiety, and stress. There are quite a several studies that examine the relationship between self-isolation and a person's stress level. This paper tries to find out how Mind Healing Technique therapy can help someone manage stress while doing self-isolation. The method used in this research is qualitative, where data is obtained through library research and interviews as data reinforcement for this research. As a result, this study shows that Mind Healing Technique therapy can help a person cope with stress during self-isolation, so it can be concluded that Mind Healing Technique techniques can be used to manage stress, especially during self-isolation